Effect of Additional Feeding Tofu Dregs and Green Bean Flour (Vigna radiat L.) on Quality Chemistry of Broiler Meat (Gallus domesticus) - Rizka Nanda Sari; Husnarika Febriani; Syukriah Syukriah (Jurnal Biologi Tropis, 2023)
Feeding broiler chickens will have an impact on meat quality. One feed that can be used as a substitute feed is tofu dregs, because it contains crude protein, fat, crude fiber, and BETN. The peanut content per 100 grams contains protein, fat, carbohydrates, water, ash, and of fiber, making it an excellent source of protein. The aim of this research was to determine the effect of providing additional feed with tofu dregs and green bean flour on the chemical quality of meat from 35 day old broiler chickens. This research used a Completely Randomized Design (CRD) method with 4 treatments and 5 replications. The treatment consisted of P0 (treatment feed without additional feed); P1 (90% commercial feed, 5% tofu dregs, and 5% green bean flour); P2 (80% commercial feed, 10% tofu dregs, and 10% green bean flour); P3 (70% commercial feed, 15% tofu dregs, and 15% green bean flour). Data analysis used analysis of variance (one way ANOVA) and continued with the Duncan test. The results of the research showed that supplementary feeding with tofu dregs and green bean flour had a significant effect on the water content, fat content and protein content of broiler chicken meat. Providing the best feed composition to produce quality broiler chicken meat is a commercial feed composition of 80%, additional feed 10% each.